La guerre au-delà des langues : ex-Yougoslavie (1991-1999) et Tadjikistan (1992-1997) - Ksenija Djordjević Léonard (Lengas)
The wars in former Yugoslavia, on the one hand, and in Tadjikistan, on the other hand, were among the most dramatic conflicts at the end of the 20th Century, following the collapse of Communist regimes in Eastern Europe and Central Asia. Comparing various sources and news in French media, we’ll account for the views and bias in reporting on these regional conflicts. Some sources happened to focus on the ethnonationalist dimension of these conflicts, while others enhanced pragmatic and political factors. We’ll question the role of language loyalty in conflicts: it seems sociolinguistic claims actually played a far weaker role in civil wars in the Balkans and Central Asia than expected, whereas deeper geostrategic and sociopolitical factors were stronger. Nevertheless, the consequences of wars may have a conspicuous impact on sociolinguistic settings and language dynamics.